PEMANFAATAN PENGERING TENAGA SURYA DALAM PRODUKSI JAHE MERAH KERING DIKAWASAN GANDUS PALEMBANG - Utami, Nurhabibah Paramitha Eka; Diah Kusuma Pratiwi; Hendri Chandra; Randi Gaga Pisasefsio Pratama (Politeknik Negeri Sriwijaya, 2024)
The utilization of red ginger, a rhizome rich in benefits, as a product with high market value can be achieved through the use of simple solar drying technology. However, there is still limited understanding of harnessing solar energy as a freely available drying source in nature. Community service activities aim to provide the basic theory of how to dry red ginger using solar energy, with the hope of enhancing community empowerment and contributing to economic self-reliance efforts. The target audience for this activity includes housewives, youth groups (Karang taruna), mosque youth associations, and local farmers in the MPD RT 02 Gandus Palembang area. The results of this activity show that the participants were highly enthusiastic in participating in discussions and Q&A sessions regarding the process of drying red ginger to create products with higher market value